A Review on Chlamydial Diseases in Animals: Still a Challenge for Pathologists?. Issue 3 (May 2018) - Borel, Nicole; Polkinghorne, Adam; Pospischil, Andreas
Chlamydiae have a worldwide distribution causing a wide range of diseases in human hosts, livestock, and companion animals as well as in wildlife and exotic species. Moreover, they can persist in their hosts as asymptomatic infections for extended periods of time. The introduction of molecular techniques has revolutionized the Chlamydia field by expanding the host range of known chlamydial species but also by discovering new species and even new families of bacteria in the broader order Chlamydiales . The wide range of hosts, diseases, and tissues affected by chlamydiae complicate the diagnosis such that standard diagnostic approaches for these bacteria are rare. Bacteria of the Chlamydiales order are small and their inclusions are difficult to detect by standard microscopy. With the exception of avian and ovine chlamydiosis, macroscopic and/or histologic changes might not be pathognomic or indicative for a chlamydial infection or even not present at all. Moreover, detection of chlamydial DNA in specimens in the absence of other methods or related pathological lesions questions the significance of such findings. The pathogenic potential of the majority of recently identified Chlamydia -related bacteria remains largely unknown and awaits investigation through experimental or natural infection models including histomorphological characterization of associated lesions. This review aims to summarize the historical background and the most important developments in the field of animal chlamydial research in the past 5 years with a special focus on pathology. It will summarize the current nomenclature, present critical thoughts about diagnostics, and give an update on chlamydial infections in domesticated animals such as livestock, companion animals and birds, as well as free-ranging and captive wild animals such as reptiles, fish, and marsupials.